Pemodelan Bawah Permukaan Berdasarkan Nilai Kecepatan Gelombang Kompresi (vp) di Kawasan Rembesan Hidrokarbon Sangubanyu, Jawa Tengah - FATMA (JURNAL TEKNOSAINS KODEPENA, 2024)
Sangubanyu is located in Central Java, Indonesia, besides having some hot springs it also has crude oil seepages that have been known since 1971, to understand the cause of these seepages subsurface structure analysis is needed by recording microtremor data at 63 points. The HVSR Method is used to process micrometer data to find subsurface conditions by wave velocity, Compressional wave velocity (vp) is part of this method. vp data could be used to interpret the layer types of subsurface conditions. The southern of the study area has about 112 to 1182 m/s of vp, and the northern has about 506 to 2944 m/s, the differential of these values could be interpreted as a fault with the southern relatively moving down from the northern, there is a little distance between this fault and the crude oil seepages, it is possible that the fracture that occurs by faults was creating secondary porosity in volcanic rock and becomes a migration route for the crude oil flows to the surface.